Pembangunan modul kurikulum intergenerasi berasaskan perkongsian kemahiran / Ngu Kee Shing - Ngu, Kee Shing (2016)
This study aimed at developing an intergenerational curriculum module based on skill sharing among the older generation and secondary school students. The module development was targeted at demonstrating how the module can be used in efforts to breach the gap between the generations and to give an opportunity to the older generation to make a meaningful contribution through the intergenerational program. This study used the Design and Development Research approach first introduced by Richey dan Klein (2007) that consists of three phases. The first phase involved needs analysis using the questionnaire administered on 618 senior citizens to identify their needs in building the intergenerational curriculum module. The second phase used the Fuzzy Delphi approach to develop a module based on the views and consensus of a 21- member panel of experts. The threshold value (d) was calculated to verify the consensus of experts toward all the questionnaire items. Three experts were selected to revise the prototype module. The third phase was the module usability evaluation using semi structured interviews with 10 students and seven senior citizens. Semi structured interviews were carried out on the sample to evaluate the usability of the intergenerational curriculum module. Findings from the first phase show that the majority of senior citizens had confidence and were willing to share their time and skills with the secondary school students. This shows that there exists a need for developing an intergenerational curriculum module based on skills for senior citizens and students. Findings from the second phase resulted in development of the module made up of the design, main module components, and 30 activities that need to be put into the intergenerational curriculum module. Three classifications of intergenerational programs were suggested (elders serve the youth, shared program and reciprocal mutual learning). The third phase findings show that the sample was satisfied with the intergenerational activities, duration and location afforded by the module. The third phase findings also show that the intergenerational curriculum module had four main strengths: the module gave opportunity and space for students and senior citizens to interact and communicate, share their skills, give opportunities for students to help the aged and generate mutual respect and make the aged feel needed. The intergenerational curriculum module based on skill sharing produced by this study can be used as a guideline for the Ministry of Education, the Ministry of Women, Family and Community Development, Senior Citizen Associations, and selected agencies when carrying out intergenerational programs in future.